A statistical quality control study on YKK Philippines, Inc. - Baluyot, Danica (College of Engineering, 2005)
The company under study, YKK Philippines Inc., is a 22 year old company under Yoshida Kogyo Kabushiki, Inc. in Japan. This company is the biggest supplier of fastener products such as zipper, snaps and buttons, and textile notions. The focus product of the study is the metal slider which composes 30 percent of the company's total sales. With the use of the various statistical tools, the group identified painting defects as the company's major problem (which caused 78.08 percent of the problems). The rest of the problems, like mis-setting of wire (which causes 65 percent of the wastage in the eccentric process) were not tackled since the problem is due mainly to human error but recommendations were given in how to minimize it. Painting problems however cause higher costs for the company. Rework costs for painting has a monthly of average Php13,260 for this year while eccentric rework costs (mis-setting of wire) average Php8,890.075. The constructed control charts showed that the initial process is out-of-control. The group made necessary adjustmets in order to introduce some sort of statistical control into the process. After ensuring control, process capability ratios were computed. These computed capability ratios showed that the process is not centered and the process potential still remains undesirable. The group recommends abolishment of slider importation in favor of local manufacturing. Paints used should be of top quality to eliminate peeling problems. The company should also emphasize employee training to reduce human error in machine handling. Comprehensive on-site training is being done to avoid this. A Training Plan is made available for the training of new operator. There are available work instructions, Procedures Manual and Quality Plan to be used in the training. Regular machine maintenance should also be ensured to avoid abrupt machine breakdowns. A stricter quality control policy should be endeavored to somehow reduce defects. Lastly, the painting department needs to come up with a final mixing procedure standard to avoid producing blends unacceptable to quality inspectors and customers.